Die Politik der Echokammer: Wisconsin und die ideologische Polarisierung der USA - Lütjen, Torben (transcript, 2016)
In the USA today there are two political camps – Democrats and Republicans, Liberals and Conservatives – operating in a state of existential enmity. But what explains the deep ideological divides that pervade the country? In his book, Torben Lütjen shows how in the USA a country has disintegrated into a series of echo chambers; virtual and social spaces that are populated by the like-minded and have become radicalised through the lack of opposition. Special focus is given to Wisconsin, in the Midwest: here, through the example of two extreme Democrat and Republican strongholds, one sees the paradigmatic embodiment of the modern conflict shaping the USA.